AN EXPLORATORY STUDY ON INTERFERENCE ERRORS FROM MALAY LANGUAGE TRASNFER TO MANDARIN LEXICON LEARNING - Ling, Lee Hui; Lateh, Nor Hazwani Munirah; Liwu, Hasan Muhammad Ma (PEOPLE: International Journal of Social Sciences, 2019)
Language transfer is one of the main factors affecting foreign language learner from learning a target language well. In Malaysia, the number of non-Chinese students learning Mandarin is increasing. However, differences in their language and cultures could impose more difficulties to the non-Chinese students when learning the language. The present study explored the interference errors from Malay language to Mandarin learning of non-Chinese students in terms of lexicon. To this end, learner corpus containing collection of the students’ compositions, dialogues and examination scripts was compiled and analyzed in the study. Four types of lexicon interference errors were focused on, namely (1) improper usage of words (2) word orders error (3) improper usage of collocation and (4) improper usage of culture images. The findings reveal the highest interference error occurs in improper usages of words followed by word order errors, improper usages of collocation and improper usages of culture images. The finding calls for a more effective teaching to be incorporated to raise the students’ awareness on the negative transfer of their native language into Mandarin lexicon learning.